"HEADS UP" DIGITALLY ASSISTED SURGICAL VIEWING FOR RETINAL DETACHMENT REPAIR IN A PATIENT WITH SEVERE KYPHOSIS. Issue Volume 12:Issues 3(2018) (2018) - Skinner, Cassandra C.; Riemann, Christopher D.
Abstract : Purpose: To describe the surgical approach with a screen-based "heads up" digital viewing technology for the successful repair of a retinal detachment in a patient with severe kyphosis. Methods: Case report. Results: An 89-year-old man with vision loss in the left eye from a macula-involving retinal detachment of 4 weeks was scheduled for pars plana vitrectomy and retinal detachment repair. The patient had severe thoracic kyphosis, causing a fixed spinal flexion that presented a significant challenge to traditional intraoperative positioning and management. Surgery was performed using the NGENUITY system for primary surgical viewing, the surgeon operating heads up, and the patient in Trendelenburg position. There were no intraoperative or postoperative complications. Visual acuity improved to 20/80 and the retina remained attached with 11 weeks of follow-up. Conclusion: Heads up digitally assisted viewing technology may be useful or preferred for patients requiring vitreoretinal surgery in the setting of severe musculoskeletal limitations or other positioning challenges. Abstract : Musculoskeletal diseases, such as kyphosis, increase in prevalence with age and can challenge traditional supine ophthalmic surgery positioning.The authors present a case where screen-based heads up digital viewing technology aided in overcoming obstacles with patient positioning in an individual with severe kyphosis and a retinal detachment.